2017
DOI: 10.1002/pssr.201700226
|View full text |Cite
|
Sign up to set email alerts
|

Self‐Assembled Silver–Gold Nanoisland Films on Glass for SERS Applications

Abstract: We present a study of resonant optical properties of gold-protected silver nanoisland films. Silver nanoislands were grown on a glass substrate using out-diffusion technique, the growth was followed by the deposition of nanometer-thick gold coatings. Scanning electron microscopy and optical spectroscopy were used to characterize morphology and extinction spectra of the grown combined silver-gold nanostructures. Micro Raman spectroscopy of the combined nanoislands has demonstrated their signal enhancement facto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 34 publications
1
11
0
Order By: Relevance
“…On the other hand, SERS tags with high sensitivity and stability are also an important factor in bacterial detection. Silver-coated gold nanoparticles (Au@AgNPs) are an excellent SERS substrate which shows higher SERS activity and more uniformity of particle size distribution compared with traditional pure AgNPs and AuNPs 25,26. However, the poor stability of Au@Ag NPs will limit their application.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, SERS tags with high sensitivity and stability are also an important factor in bacterial detection. Silver-coated gold nanoparticles (Au@AgNPs) are an excellent SERS substrate which shows higher SERS activity and more uniformity of particle size distribution compared with traditional pure AgNPs and AuNPs 25,26. However, the poor stability of Au@Ag NPs will limit their application.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, core-shell approaches such as Au@Ag nanoparticles serve as excellent SERS substrates, since significantly higher EFs are expected for silver as compared with gold. [79][80][81] When using gold nanomaterials for instance, one drawback might be the high photothermal conversion efficiency provided under resonance excitation, which can be destructive for biological samples. Thus, the rational choice of the shape and composition, and tuning of the excitation spectral window for a minimal heating and photodegradation are the key elements in using nanostructured probes in biosensing.…”
Section: Rational Design Of High-performance Sers Substratesmentioning
confidence: 99%
“…The above results demonstrated that the substrate had higher response sensitivity to R6G probe molecules than similar structured substrates prepared by other scalable methods reported in the literature. 17,20,37 Theoretically, when the spacing between silver nanoparticles was greater than the resolution of the optical microscope, the SERS spectrum collected at each time was actually derived from single nanoparticle since nanoparticles were discretely grown in situ. The resolution of the objective lens used in the Raman test was about 1 μm, and the number of silver particles contained in 1 μm 2 was very small, or even only one.…”
Section: Resultsmentioning
confidence: 99%